P-017 Triple therapy versus dual antiplatelet therapy for dolichoectatic vertebrobasilar fusiform aneurysms treated with flow-diverters: the last frontier?. (23rd July 2022) - Siddiqui, A; Monteiro, A; Hanel, R; Kan, P; Mohanty, A; Cortez, G; Rabinovich, M; Matouk, C; Sujijantarat, N; Ebersole, K; Fry, L; Natarajan, S; et al.
Abstract : Introduction: Dolichoectatic vertebrobasilar fusiform aneurysms (DVBFA) have poor natural history with worsening of brainstem compression and eventual rupture within a few years. Flow-diversion is feasible, but even under dual-antiplatelet therapy (DAPT) it carries high risk of perforator occlusion. More elaborated antithrombotic therapies are warranted to keep the patency of perforators while vessel remodeling occurs. We compared DAPT plus oral anticoagulation, strategy called triple therapy (TT), and DAPT alone in patients with DVBFAs treated with flow-diverters (FD). Methods: Vertebrobasilar aneurysms treated with flow diversion at 8 United States centers were retrospectively reviewed. Only dolichoectactic aneurysms involving at least one segment of the basilar artery were included. All patients were DAPT 5 to 7 days prior to intervention and continued for at least 6 months after the procedure. All patients received heparin during the procedure. For patients treated with triple therapy, anticoagulant drug, dosage and duration were decided at the discretion of each operator. Baseline characteristics, clinical and angiographic outcomes were compared. Results: Twenty-three patients were included (11 triple therapy vs 12 DAPT) There were no significant differences in age, male sex, and presentation with compressive or ischemic symptoms between the groups (triple therapy, 72.7% vs 58.3%; P=0.668). The rate of moderate to severe disability (mRS≥3) prior to procedure was 36.4% in the triple therapy and 8.3% in the DAPT group (P=0.316). Atherosclerosis in the vertebrobasilar circulation was present in 54.5% and 41.6% of triple therapy and DAPT group, respectively (P=0.683). Maximum diameter of dilatation was not significantly different between the groups (triple therapy, 15.7 mm vs DAPT, 12 mm, P=0.373). Intra-aneurysmal thrombus was present in 54.5% and 41.7% of patients treated with triple therapy and DAPT, respectively (P=0.683). There was no significant difference in the mean number of devices or rate of adjunctive coiling between the groups. Procedural success without complications was achieved in 100%. The triple therapy and DAPT groups had a median clinical follow-up of 600 days (IQR 310–780) and 177 days (IQR 48–1597), respectively (P=0.211). When considering only events occurring during anticoagulant use in the triple therapy group, the rate of ischemic stroke was 9.1% in comparison to 33.3% in the DAPT group (P=0.316). The rate of worsening of initial symptoms was 0% in the triple therapy group and 41.7% in the DAPT patients (P=0.03). The overall rate of mRS decline from pre-procedure to last follow-up was 0% in the triple therapy group and 66.7% in the DAPT group (P=0.0013). The overall rate of hemorrhagic complications was 36.3% in the triple therapy and 9.1% in the DAPT group (P=0.316). The rate of moderate to severe disability (mRS ≥3) at last follow-up was 27.3% in the triple therapy group and 75% in the DAPT, respectively (P=0.039). Complete occlusion was achieved in 27.3% and 50% of the triple therapy and the DAPT groups, respectively (P=0.387). Conclusions: Patients with dolichoectatic VBFAs treated with flow-diversion and kept under triple therapy had less ischemic strokes, less progression of symptoms and overall better outcomes at last follow-up than similar patients kept under DAPT. Disclosures: A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc., . 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical, . A. Monteiro: None. R. Hanel: None. P. Kan: None. A. Mohanty: None. G. Cortez: None. M. Rabinovich: None. C. Matouk: None. N. Sujijantarat: None. K. Ebersole: None. L. Fry: None. S. Natarajan: None. B. Owusu-Adjei: None. S. Ortega-Gutierrez: None. J. Vivanco-Suarez: None. A. Wakhloo: None. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 3; C; Medtronic. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical.